A SYSTEMATIC REVIEW OF PARENTS' PATTERNS AND BARRIERS TO BRINGING CHILDREN TO THE DENTIST - Trandyana, Reindasty; Badruddin, Iwany; Adiatman, Melissa; Bahar, Armasastra (Ridwan Institute, 2024)
Caries at an early age is a global problem that affects almost half of preschool children, the prevalence of early childhood caries (ECC) globally varies widely. One of the causes of caries in children less than 5 years old is the delay in the first visit to the dentist. The purpose of this study is to identify patterns of service utilization and obstacles that cause low visits to dentists so that programs can be planned that are able to increase the number of dental visits. A literature review was conducted using PubMed, ProQuest, SpringerLink, and ScienceDirect databases with keywords such as Dental care, Dental attendance, dental utilization, and Oral health promotion. The data were then thematically analyzed to uncover trends, common challenges, and effective interventions across the literature. The results of this systematic review show a pattern in visiting the dentist, including visiting for routine dental checkups, preventive treatments, acute pain conditions that have been experienced and trauma. The patterns of use of dental and oral health services in children are influenced by the level of parental education, the type of dental health care that is covered by limited health insurance, low socio-economic factors, socio-demographic factors, and lack of adequate insurance. This study aims to offer valuable insights into the patterns of dental care utilization and the obstacles preventing higher visitation rates to dental services. The findings are synthesized to highlight consistencies and gaps, ultimately providing insights to inform the development of programs aimed at improving dental visit rates.